The muscle - fat duel or why obese children are taller? - Ralt Dina (BMC, 2006)
Abstract Background Obesity the epidemic of our times appears to be a problem that is easy to resolve: just eat less and move more. However, this very common condition has turned out to be extremely troublesome, and in some cases even irreversible. Methods The interplay between less muscle and more fat tissue is discussed from physiological perspectives with an emphasis on the early years of childhood. Results It is suggested that the coordinated muscle-fat interactions lead to a fluctuating exchange economy rate. This bodily economic decision, slides between thrift (more fat) and prodigal (more muscle) strategies. The thrift strategy results not only in obesity and less physical activity but also in other maladies which the body is unable to manage. What leads to obesity (less muscle, more fat) might be very difficult to reverse at adulthood, prevention at childhood is thus recommended. Conclusion Early recognition of the ailment (low muscle mass) is crucial. Based on studies demonstrating a 'rivalry' between muscle build-up and height growth at childhood, it is postulated that among the both taller and more obese children the percentage of children with lower muscle mass will be higher. A special, body/muscle-building gymnastics program for children is suggested as a potential early intervention to prevent the ill progress of obesity.